Perinatal depression in times of COVID-19: the role of social media on the Internet - Bermejo-Sánchez, Fredy R. (2020)
Public health emergencies such as COVID-19 pandemic could lead to situations of extreme stress, anxiety and depression in women in the perinatal period. Perinatal depression may lead to multiple negative consequences for mothers, newborns, and their relatives. Appropriate use of social media may be a valuable supporting tool for women during this stage of their lives. This paper describes the role of social media in the Internet for supporting pregnant women and mothers with depression, particularly in global public health emergencies such as the COVID-19 pandemic. Social media may contribute to support health and wellness by facilitating social interaction, building communities, normalizing help-seeking behavior, inspiring healthy lifestyle changes, and promoting medical research. It is essential to adequately instruct women in the perinatal stage in digital health literacy including the efficient use of social media for socio-emotional support and assuring the quality of the information circulating in social media and in Internet for proper decision-making.